Suicide risk assessment: A study among university students in the health area (Research, Society and Development, 2021)
Admission to the university represents a phase of change in social life and daily activities with autonomy and freedom for the student, and implies responsibilities in relation to academic charges. We realize that, as a result of these factors, many situations can make the student vulnerable to mental disorders. The objective of the study was to evaluate the mental health profile in relation to suicide risk among university students of a higher education institution. It is a descriptive and transversal approach study, with prospective temporal directionality. The research was conducted in a private university in the municipality of São Luís-MA, with a total sample of 451 university students from the Nursing, Dentistry, Psychology and Medicine courses. For data collection, a Sociodemographic Data Questionnaire and the Columbia Suicide Risk Assessment Scale (C-SSRS) were used. The research obeyed the ethical aspects according to Resolution 466/12. In the results, 80.3% were female, 53.7% were between 21 and 25 years old, 90.9% had no children and 43.0% were Catholic. According to C-SSRS, 39.5% of the students wanted to be dead, 29.3% wanted to kill themselves and 12.4% thought about how to take their own lives. Therefore, the university needs to build affective bonds with its students in order to improve its prognosis still in the academic environment. Thus, the study calls attention to the need to build and/or improve centers to meet the demands of mental health within universities to deal with such a situation.